Changes in the subpopulation composition of lymphocytes in women with genital endometriosis - Dildora Ismoilova Urgench, Nargiza Magzumova, Dilorom Musohodjaeva (International Journal of Advanced Science and Technology, 2020)
56 patients with genital endometriosis were examined. Of these, 26 had internal endometriosis, and 30 had external genital endometriosis. 18 practically healthy women made up a control group. All examined women were examined the state of the immune system (cellular immunity, phagocytosis and cytokine status). It was found that in patients with endometriosis, the level of T-lymphocytes and its subpopulation composition were reduced, and the level of killer activity varied in different ways depending on the form of genital endometriosis. Functional activity of neutrophils changed only in the group of women with EGE.